A New Twist in Managing Cogongrass - Rick Williams (EDIS)
FOR-185, a 4-page illustrated fact sheet by Rick Williams, presents the results of several experiments evaluating various herbicides used to control this invasive, nonnative plant in Florida. Includes references. Published by the UF School of Forest Resources and Conservation, May 2008.